Action threshold for Thrips palmi (Thysanoptera: Thripidae) on snap beans in the Cauca Valley, Colombia - BUENO, JUAN MIGUEL; CARDONA-M., CÉSAR (Revista Colombiana de Entomología, 2003)
Since its introduction to Colombia in 1997, the melon thrips, Thrips palmi Karny, has become one of the main pests of snap beans in the Cauca Valley. Al present, this species is the target of excessive use of insecticides. One way to rationalize the use of pesticides is to apply them at critical infestation levels, known as action thresholds. To develop an action threshold for T. pelmi, two complete randomized blocks trials and one in Latin square design were conducted in Pradera (980 meters above sea level, 23 ºC). In these experiments, snap bean response to increasing infestation levels (1 - 17 adults/leaflet) was measured. A negative relationship was found between infestation levels and yields that can be explained by the regression y = 12926- 695.9x, an average of three trials Is. Using a loss function of 695.9 kg/ha per adult/leaflet, an average action threshold of 7.0 adults per leaflet was calculated. When infestation levels were maintained below this threshold, actual infestation levels through the crop cycle ranged from 3 to 4 adults/leaflet. The potential use of this action threshold in a management system is discussed.